Судьба: роман / Петр Проскурин - Проскурин Петр Лукич (Профиздат, 1990)
Экземпляры: аб. (1991) / Инвентарный номер: 32959 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 82 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44